Revision of the Statutes of New Jersey 232-33 (1877) - (:unkn) unknown (My University, 1877)
An act for the punishment of crimes against the public peace, 31: If any person shall by word, message, letter, or any other way, challenge another to fight a duel, with a rapier, or small-sword, back-sword, pistol, or other dangerous weapon, or shall accept a challenge, although not duel be fought, or knowingly be the bearer of such challenge, or shall any way abet, prompt, encourage, persuade, seduce, or cause any person to fight a duel, or to challenge another to fight a duel, every person so offending shall be deemed guilty of a misdemeanor
Keywords: DUELING